(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The favorable trade volume of a country in the present dynamic world has great significance on the country’s economic growth and prosperity. In this direction, the most fabulous step that India has taken is the adoption of economic reforms in 1991. The conservative approaches of India’s foreign trade had thrown out and adopted barrier-less approaches to boost the country’s external trades. The South Asian Association for Regional Cooperation (SAARC) comprising eight states of the south Asian countries was formed to enhance the volume of trade among the member countries. In this connection, the present paper is an attempt to analyze the changes that occurred due to adoption of new trade policies in India’s trade performance with SAARC countries as well as with rest of the world. The secondary data from various sources are collected and used to analyze the India’s trade performance with SAARC countries after adoption of economic reforms in 1991. The analysis of the study indicates a positive relationship in India’s trade performance and adoption of economic liberalization in 1991. It is also endorses from the analysis of the study that growth of trade with SAARC countries shows a positive trend compare to India’s overall trade performance with rest of world.